Exploring the alignment between postsecondary education programs and earnings: An examination of 2005 Ontario graduates - Frank, Kristyn; Walters, David (Canadian Journal of Higher Education, 2012)
This study examines the influence that field of study and level of post-secondary education have on the earnings of recent graduates in Ontario. Graduates of trades, community college, and university programs are compared. Results suggest that graduates of applied and technical programs obtain higher earnings within two years of graduation than graduates of liberal arts programs. University graduates also fare better than college and trades graduates, whereas male graduates of trades programs are found to obtain higher earnings than college graduates. This study provides updated information for policy officials involved with allocating government funding to post-secondary education in Ontario.